Disruption of an exon splicing enhancer in exon 3 of MLH1 is the cause of HNPCC in a Quebec family. Issue 2 (27th May 2005) - McVety, S; Li, L; Gordon, P H; Chong, G; Foulkes, W D
Abstract : Background: A 3 bp deletion located at the 5′ end of exon 3 of MLH1, resulting in deletion of exon 3 from RNA, was recently identified. Hypothesis: That this mutation disrupts an exon splicing enhancer (ESE) because it occurs in a purine-rich sequence previously identified as an ESE in other genes, and ESEs are often found in exons with splice signals that deviate from the consensus signals, as does the 3′ splice signal in exon 3 of MLH1 . Design: The 3 bp deletion and several other mutations were created by polymerase chain reaction mutagenesis and tested using an in vitro splicing assay. Both mutant and wild type exon 3 sequences were cloned into an exon trapping vector and transiently expressed in Cos-1 cells. Results: Analysis of the RNA indicates that the 3 bp deletion c.213_215delAGA (gi:28559089, NM_000249.2), a silent mutation c.216T→C, a missense mutation c.214G→C, and a nonsense mutation c.214G→T all cause varying degrees of exon skipping, suggesting the presence of an ESE at the 5′ end of exon 3. These mutations are situated in a GAAGAT sequence 3 bp downstream from the start of exon 3. Conclusions: The results of the splicing assay suggest that inclusion of exon 3 in the mRNA is ESE dependent. The exon 3 ESE is not recognised by all available motif scoring matrices, highlighting the importance of RNA analysis in the detection of ESE disrupting mutations.